Ectopic Premolar Tooth in the Sigmoid Notch. (28th July 2016) - Törenek, K.; Akgül, H. M.; Bayrakdar, I. S.
Abstract : Impaction of a mandibular premolar is relatively uncommon. Ectopic placement is more unusual and there has been no discussion in the literature of an ectopic mandibular premolar in the coronoid process. In this case report, we present an impacted ectopic mandibular permanent premolar in the sigmoid notch (incisura mandibulae) region. Etiology of the tooth and treatment options are discussed and illustrated by Cone Beam Computed Tomography (CBCT) images.